Translating an Evidence-Based Lifestyle Intervention Program Into Primary Care: Lessons Learned. Issue 4 (July 2013) - Blonstein, Andrea C.; Yank, Veronica; Stafford, Randall S.; Wilson, Sandra R.; Rosas, Lisa Goldman; Ma, Jun
The E-LITE (Evaluation of Lifestyle Interventions to Treat Elevated Cardiometabolic Risk in Primary Care) trial evaluated the feasibility and potential effectiveness of translating an evidence-based lifestyle intervention for the management of obesity and related risk factors in a primary care setting. Delivered by allied health care providers, the intervention promoted at least 7% weight loss and at least 150 minutes per week of moderate-intensity physical activity through gradual, sustainable lifestyle changes. Activities included interactive group lessons, food tasting, guided physical activity, and technology-mediated self-monitoring and behavioral counseling. This article discusses insights and potential areas for improvement to strengthen program implementation for dissemination of the E-LITE program to other primary care settings. We focus on (a) the role of allied health professionals in program delivery, (b) strengthening program integration within a primary care clinic, and (c) the use of information technology to extend the reach and impact of the program. Our experience shows the feasibility of implementing an evidence-based lifestyle intervention program combining group-delivered nutrition and behavioral counseling, physical activity training, and technology-mediated follow-up in a primary care setting. Challenges remain, and we offer possible solutions to overcome them.